2015
DOI: 10.1016/j.geomorph.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Taking the river inside: Fundamental advances from laboratory experiments in measuring and understanding bedload transport processes

Abstract: Bedload transport in gravel-bed rivers impacts channel stability, the lifespan of hydraulic structures, physical components of aquatic habitat, and long-term channel evolution. Field measurements of bedload transport are notoriously difficult, which precludes understanding many of the processes and mechanics associated with grain motion. Such uncertainties are exacerbated when using bedload transport equations, most of which were derived using data from a single river or set of laboratory flume experiments. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 127 publications
(199 reference statements)
0
43
1
Order By: Relevance
“…Still little is known on the behavior of an armor under peak flow (Vericat et al, 2006;Yager et al, 2015). Studies have demonstrated that, during peak flow, armored surfaces can be stable and persist or broken and reform during the waning phase of the flood event.…”
Section: Introductionmentioning
confidence: 99%
“…Still little is known on the behavior of an armor under peak flow (Vericat et al, 2006;Yager et al, 2015). Studies have demonstrated that, during peak flow, armored surfaces can be stable and persist or broken and reform during the waning phase of the flood event.…”
Section: Introductionmentioning
confidence: 99%
“…Yager et al. () proposed several key areas to further investigate sediment transport in gravel‐bed rivers under unsteady conditions, including the scaling of experimental hydrographs, and isolating the influence of different hydrograph characteristics on bedload transport processes. At present, there appears to be little consensus in the literature regarding the appropriate scaling of experimental hydrographs, particularly the duration.…”
Section: Discussionmentioning
confidence: 99%
“…This notion of threshold is often criticized and might not exist when considering a stochastic sediment transport (Einstein, ; Lavelle and Mofjeld, ; Yager et al. ). The frictional force exerted by the flow is referred to as the bed shear stress .…”
Section: Introductionmentioning
confidence: 99%